Records management for dummies - Richardson, Blake (--For dummies., 2012)
Here's what you should know to manage data records efficiently With proper electronic data management, your business can lower costs, improve efficiency, eliminate duplication, and be protected in the event of a lawsuit. This book provides an overview of records management solutions and implementation strategies in plain, non-technical English. Step-by-step instructions show you how to begin managing records and information and how to maintain the program once you have it established. Sample forms for inventory, scheduling, and necessary documentation are also available on the companion websit.